A realistic evaluation of integrated offender management in one English county: a partnership for desistance? - Evans, Emily Victoria (2016)
This thesis presents the findings of an in-depth realistic evaluation of the Integrated Offender Management (IOM) approach in one English county. IOM is a multi-agency approach, promoted by government, to managing prolific offenders, with the aim of moving them towards desistance from crime.